Keragaman Genetik dan Filogenetik Kepiting Biola (Uca Spp.) di Pesisir Pantai Jailolo, Kabupaten Halmahera Barat - Abdurrachman Baksir; Nebuchadnezzar Akbar; Firdaut Ismail (Universitas Diponegoro, 2022)
The types of crabs that inhabit coastal and mangrove areas are violin crabs (Uca spp.). The research genetic aspects is important to be able to explain the current status of crabs. The research location in the villages of Payo (geothermal water area) and Tuada (tourist sites). Sampling was done purposively, namely the mangrove area that received the flow of geothermal water sources (Payo Village = 4 samples) and the mangrove area that did not get any influence (Tuada Village = 2 samples). Amplification of Biola crab DNA (Uca Spp.) using primer jgLCO1490 and jgHCO2198 Sequences were analyzed with MEGA5 (Molecular Evolutionary Genetic Analysis) software, genetic distance, DnaSP 4.0 diversity of haplotype (Hd) and nucleotide diversity (π). and Network 4.6 haplotype distribution. Enviromental parameters collected include (temperature, pH land, pH water, salinity and substrate). The results environmental parameters show that differences values at two locations. Identification species crab found family Ocypodidae, genus Uca with species of perplexa, annulipes, crassipes and lactea. The results of genetic matching were found, similar to the results of morphological identification. Genetic diversity was found highly with nucleotides and haplotype varitions. Phylogenetic reconstruction of Uca Spp crabs shows the kinship that occurs between species, although there is a gap (gap) between different species of location. Genetic distance and Fixation Index (Fst) analysis which also shows genetic proximity between species and strong genetic flow between species, despite different locations. Jenis kepiting yang mendiami wilayah pesisir dan mangrove adalah kepiting biola (Uca spp.). Penelitian tentang aspek genetik begitu penting untuk dapat menjelaskan status kepiting saat ini. Lokasi penelitian di desa Payo (Daerah sumber air panas bumi) dan Tuada (Lokasi wisata). Sampling dilakukan secara purposive yaitu area mangrove yang mendapatkan aliran sumber air panas bumi (Desa Payo = 4 sampel) dan tidak mendapatkan pengaruh (Desa Tuada = 2 sampel). Amplifikasi DNA kepiting Biola (Uca spp) menggunakan primer jgLCO1490 dan jgHCO2198 Sekuen dianalisis dengan software MEGA5 (Molecular Evolutionary Genetic Analysis), jarak genetik, DnaSP 4.0 keanekaragaman haplotype (Hd) dan keanekaragaman nukleotida (π) dan Network 4.6 distribusi haplotipe. Parameter lingkungan diukur meliputi (suhu, pH air, pH tanah, salinitas dan substrat). Hasil pengukuran parameter lingkungan memperlihatkan perbedaan nilai kedua lokasi. Identifikasi jenis kepiting ditemukan famili Ocypodidae, genus Uca dengan spesies perplexa, annulipes, crassipes dan lactea.. Keragaman genetik sangat tinggi dengan jumlah nukleotida dan haplotipe yang bervariasi. Rekonstruksi filogenetik memperlihatkan kekerabatan terjadi antar spesies, meskipun terdapat adanya jarak (Gap) antar spesies yang berbeda lokasi. Analisis jarak genetik dan analisis Fixation Index (Fst) yang juga memperlihatkan adanya kedekatan genetik dan aliran genetik yang kuat antar spesies, meskipun berbeda lokasi.